Economics for the common good - Tirole, Jean; Rendall, Steven (Princeton, New Jersey Princeton University Press, 2017)
When Jean Tirole won the 2014 Nobel Prize in Economics, he suddenly found himself being stopped in the street by complete strangers and asked to comment on issues of the day, no matter how distant from his own areas of research. His transformation from academic economist to public intellectual prompted him to reflect further on the role economists and their discipline play in society. The result is Economics for the Common Good, a passionate manifesto for a world in which economics, far from being a "dismal science," is a positive force for the common good. Economists are rewarded for writing technical papers in scholarly journals, not joining in public debates. But Tirole says we urgently need economists to engage with the many challenges facing society, helping to identify our key objectives and the tools needed to meet them. To show how economics can help us realize the common good, Tirole shares his insights on a broad array of questions affecting our everyday lives and the future of our society, including global warming, unemployment, the post-2008 global financial order, the euro crisis, the digital revolution, innovation, and the proper balance between the free market and regulation. Providing a rich account of how economics can benefit everyone, Economics for the Common Good sets a new agenda for the role of economics in society. -- Provided by publisher.
Introduction : whatever happened to the common good? : -- Itinerary -- The relationship between society and economics -- The economist's profession -- Institutions -- A window on our world -- The common thread -- Part I. Economics and society : -- 1. Do you like economics? : -- What prevents our understanding economics -- The market and other ways of managing scarcity -- How to make economics better understood -- 2. The moral limits of the market : -- The moral limits of the market or market failure? -- The noncommercial and the sacred -- The market, a threat to social cohesion? -- Inequality -- Part II. The economist's profession : -- 3. The economist in civil society : -- The economist as public intellectual -- The pitfalls of involvement in society -- A few safeguards for an essential relationship -- From theory to economic policy -- 4. The everyday life of a researcher : -- The interplay between theory and empirical evidence -- The microcosm of academic economics -- Economists : foxes or hedgehogs? -- The role of mathematics -- Game theory and information theory -- An economist at work : methodological contributions -- 5. Economics on the move : An agent who is not always rational : -- Homo psychologicus -- Homo socialis -- Homo incitatus : the counterproductive effects of rewards -- Homo juridicus : law and social norms -- More unexpected lines of inquiry -- Part III. An institutional framework for the economy : -- 6. Toward a modern state : -- The market has many defects that must be corrected -- The complementarity between the market and the state and the foundations of liberalism -- Politicians or technocrats? -- Reforming the state : the example of France -- 7. The governance and social responsibility of business : -- Many possible organizations, but few are chosen -- And what is business's social responsibility? -- Part IV. The great macroeconomic challenges : -- 8. The climate challenge : -- What is at stake in climate change? -- Reasons for the standstill -- Negotiations that fall short of the stakes involved -- Making everyone accountable for GHG emissions -- Inequality and the pricing of carbon -- The credibility of an international agreement -- In conclusion : putting negotiations back on track -- 9. Labor market challenges : -- The labor market in France -- An economic analysis of labor contracts -- Perverse institutional incentives -- What can reform achieve and how can it be implemented successfully? -- The other great debates about employment -- The urgency -- 10. Europe at the crossroads : -- The European project : from hope to doubt -- The origins of the Euro crisis -- Greece : much bitterness on both sides -- What options do the EU and the Eurozone have today? -- 11. What use is finance? : -- What use is finance? -- How to transform useful products into toxic products -- Are markets efficient? -- Why regulate in fact? -- 12. The financial crisis of 2008 : -- The financial crisis -- The new postcrisis environment -- Who is to blame? : Economists and the prevention of crises -- Part V. The industrial challenge : -- 13. Competition policy and industrial policy : -- What is the purpose of competition? -- Where does industrial policy fit in? -- 14. How digitization is changing everything : -- Platforms : guardians of the digital economy -- Two-sided markets -- A different business model : platforms as regulators -- The challenges two-sided markets pose for competition policy -- 15. Digital economies : the challenges for society : -- Trust -- Who owns data? -- Health care and risk -- The new forms of employment in the twenty-first century -- The digital economy and employment -- The tax system -- 16. Innovation and intellectual property : -- The imperative of innovation -- Intellectual property -- Managing royalty stacking -- The institutions of innovation -- Cooperative development and open source software -- And many other debates -- 17. Sector regulation : -- What's at stake -- A fourfold reform and its rationale -- Incentive regulation -- Prices of regulated companies -- Regulation of access to the network -- Competition and universal service -- Epilogue.
Includes bibliographical references (pages 485-550) and index
Keywords: Economics; Economics -- Sociological aspects; Economic policy; Common good -- Economic aspects